A study of mode of transmission, clinical presentations, WHO and immunological staging among HIV infected children - Kumar, Durgesh; Singh, Mukesh V.; Kumar, Dinesh; Shukla, K. M.; Singh, D. K.; Singh, Dharmendra K. (International Journal of Research in Medical Sciences, 2017)
Background: The clinical manifestations of HIV infection vary widely among infants, children, and adolescent. So there is a need to study the mode of transmission, clinical presentations, WHO and immunological staging among HIV infected children. Methods: Observational analytic cross sectional study. The children who were HIV positive (confirmed by ELISA for HIV-1 and HIV-2), and attending the OPD of ART Centre and SN Children Hospital, Allahabad during period of one year. The study population consisted of 47 patients, belonging to both sexes and age of 18 months to 19 years. Detailed history was taken and full clinical examination done in all cases. CD4 count was estimated at the time of presentation. Results: Predominant mode of transmission in our study was vertical and it was present in 95% cases. Fever was the most common presenting complaint and was present in 28 (59.57%) cases. The most common clinical sign was pallor in our study, present in 37 cases (78.72%) followed by lymphadenopathy 34 (72.34%). On the basis of WHO clinical staging, most of the patients in our study were found in stage 2 .On the basis of immunological staging, 51% had no evidence of immunosuppression (stage1), 18 (38.3%) had mild to advanced immunosuppression (stage 2 and 3) and 5 (10.63%) patients were severely immunosuppressed (stage 4). Conclusion: In HIV infected children predominant mode of transmission is vertical. Fever and pallor are common clinical manifestations. Most of the patients are found in WHO clinical stage 2 and immunological stage 1.